Acute kidney injury caused by ureteral obstruction after Deflux® injection treatment for vesicoureteral reflux after pediatric kidney transplantation: a case report - Yujiro Aoki; Yuko Hamasaki; Junya Hashimoto; Ayuko Zaitsu; Maho Maeda; Masaki Muramatsu; Takeshi Kawamura; Seiichiro Shishido; Ken Sakai (BMC Urology)
Abstract Background Vesicoureteral reflux (VUR) after pediatric kidney transplantation (KT) is a frequent urologic complication. Endoscopic Deflux® injection is a treatment option. However, ureteral obstruction after Deflux® injection treatment is a potential complication that may have serious outcomes for patients who have undergone KT. We report a case of acute kidney injury (AKI) caused by ureteral obstruction with acute foreign body reaction immediately after Deflux® injection treatment for VUR after transplantation. Case presentation We encountered a 5-year-old boy who underwent living-donor KT at age 4 years because of end-stage kidney disease caused by posterior urethral valves. At 4 months after KT, VUR (grade IV) and bladder dysfunction worsening were detected by voiding cystourethrography. A second febrile urinary tract infection (UTI) was treated with endoscopic Deflux® injection in the neo-orifice of the transplanted kidney after 2 weeks of antimicrobial therapy. Postoperatively, the patient experienced a temporary decrease in urine output. Increased creatinine was observed on postoperative day 1. The renal pelvis was more dilated than it was preoperatively, and ureteral dilatation was observed. A bulge associated with Deflux® injection, consistent with the injection site, was observed in the bladder. Additionally, because the graft function continued to decline, AKI associated with ureteral obstruction after Deflux® injection treatment was diagnosed, and a ureteral stent was placed on postoperative day 4. The graft function gradually recovered. Four months later, the ureteral stent was removed. Exacerbation of hydronephrosis of the transplanted kidney was not observed, and the graft function was stable. Although the patient experienced residual VUR after KT, excretion control was continued and UTI recurrence was not observed. Conclusions Ureteral obstruction after Deflux® injection treatment for VUR after transplantation is a serious complication; therefore, treatment indications and timing should be carefully considered.